Metallic Active Sites on MoO2(110) Surface to Catalyze Advanced Oxidation Processes for Efficient Pollutant Removal - Ji, Jiahui; Aleisa, Rashed M.; Duan, Huan; Zhang, Jinlong; Yin, Yadong; Xing, Mingyang (iScience, 2020)
Advanced oxidation processes (AOPs) based on sulfate radicals (SO4⋅−) suffer from low conversion rate of Fe(III) to Fe(II) and produce a large amount of iron sludge as waste. Herein, we show that by using MoO2 as a cocatalyst, the rate of Fe(III)/Fe(II) cycling in PMS system accelerated significantly, with a reaction rate constant 50 times that of PMS/Fe(II) system. Our results showed outstanding removal efficiency (96%) of L-RhB in 10 min with extremely low concentration of Fe(II) (0.036 mM), outperforming most reported SO4⋅−-based AOPs systems. Surface chemical analysis combined with density functional theory (DFT) calculation demonstrated that both Fe(III)/Fe(II) cycling and PMS activation occurred on the (110) crystal plane of MoO2, whereas the exposed active sites of Mo(IV) on MoO2 surface were responsible for accelerating PMS activation. Considering its performance, and non-toxicity, using MoO2 as a cocatalyst is a promising technique for large-scale practical environmental remediation. [Display omitted] •The degradation rate of PMS/Fe(II)/MoO2 system is 50 times higher than that without MoO2•Fe(III)/Fe(II) cycle on (110) surface of MoO2 in PMS/Fe(II)/MoO2 system was confirmed•The metal active sites exposed to MoO2 (110) surface are responsible for PMS activation•Compared with MoS2, MoO2 co-catalytic system has less toxicity and no release of H2S Inorganic Chemistry; Catalysis; Water Resources Engineering